Pengembangan Model Sistem Informasi Berbasis Akuntansi Tingkat Harga Umum untuk Pelaporan Keuangan pada Masa Inflasi - Sri Kustriyanti; Endang Karyawati (STIA MALANG, 2026)
Historical cost-based financial reporting tends to produce information that poorly reflects changes in purchasing power under inflationary conditions, thereby potentially reducing the quality of economic decision-making. General price-level accounting is an approach to adjusting financial statements when price-level changes occur. This adjustment is beneficial for management decision-making. This study aims to develop an Inflation Accounting Information System Model based on general price-level accounting as a framework for data management and the process of converting historical financial statements into general purchasing power-based financial statements.The study employs a Design Science Research (DSR) approach, which includes problem identification, defining solution objectives, and model design. The results of the study are expected to yield a model that integrates conventional accounting data processing into financial statements whose values are adjusted based on inflation rates. The contribution of this research lies in the development of a conceptual model for an accounting information system that links the concept of general price-level accounting with information system modeling, thereby serving as a reference for the development of inflation accounting information systems in organizations. Keywords: Inflation Accounting, Accounting Information System, General Price-Level Accounting, Model, Design Science Research (DSR).